Pengaruh Work-Life Balance terhadap Subjective Wellbeing pada Polisi Wanita di Polrestabes Bandung - Mega Khansa Khairunnisa; Suhana (Bandung Conference Series: Psychology Science, 2023)
Abstract. Currently, many women work in jobs that are mostly done by men, one of which is being a police officer. For women with families, being a police officer adds a role in their lives, so a police woman needs to pay attention to her subjective wellbeing. One of the factors that influence it is by balancinng personal life and work (work-life balance). This research was conducted to see how much influence work-life balance has on subjective wellbeing of woman police officers at Polrestabes Bandung. The subjects of the study were 56 married police woman at Polrestabe Bandung. Data collection was carried out using a work-life balance measurement tool developed by Fisher et al. (2009) and adapted by Giani et al. (2019), then the subjective wellbeing satisfaction with lifescale measurement tool developed by Diener et al. (1985) and adapted by Yonathan & Yusak (2003), and the scale of positive and negative experiences developed by Diener et al. (2009) and adapted by Hanif (2019). The study used multiple linear regression analysis techniques with the result R2 = 0.703 or work-life balance giving an effect of subjective wellbeing of 70.3%. all dimensions of work-life balance have an influence on subjective wellbeing. The dimension of personal life interference with work has the highest influence, namely 23.3%, and the dimension of work interference with personal life, has the lowest influence, namely 11.9%. Abstrak. Saat ini banyak wanita bekerja pada pekerjaan yang mayoritas dilakukan oleh laki-laki, salah satunya menjadi seorang polisi. Bagi wanita yang berkeluarga, menjadi polisi menambah peran dalam hidupnya, sehingga seorang polisi wanita perlu memperhatikan subjective wellbeing pada dirinya. Salah satu faktor yang mempengaruhinya yaitu dengan menyeimbangkan kehidupan pribadi dan pekerjaan (work-life balance). Penelitian ini dilakukan untuk melihat seberapa besar pengaruh work-life balance terhadap subjective wellbeing pada polisi wanita di Polrestabes Bandung. Subjek penelitian berjumlah 56 polisi wanita di Polrestabes Bandung yang sudah menikah. Pengumpulan data dilakukan menggunakan alat ukur work-life balance yang dikembangkan oleh Fisher et al. (2009) dan diadaptasi oleh Giani et al. (2019), kemudian alat ukur subjective wellbeing satisfaction with life scale yang dikembangkan oleh Diener et al. (1985) dan di adaptasi oleh Yonathan&Yusak (2003), dan scale of positive and negative experience yang dikembangkan oleh Diener et al. (2009) dan diadaptasi oleh Hanif (2019). Penelitian menggunakan teknik analisis regresi linear berganda dengan hasil R2=0,703 atau work-life balance memberikan pengaruh kepada subjective wellbeing sebesar 70,3%. Seluruh dimensi dari work life balance memberikan pengaruh pada subjective wellbeing. Dimensi personal life interference with work memiliki pengaruh tertinggi yaitu 23,3% dan dimensi work interference with personal life memiliki pengaruh paling rendah yaitu 11,9%.